The Journey to God: Union, Purgation and Transformation within The Ascent of Mount Carmel and A Plain Account of Christian Perfection - Martyn, Stephen (The Asbury journal, 2012)
This article is both a call to Christian maturity and an appreciative recounting of how a Roman Catholic mystic, John of the Cross, helped me reclaim and love my own Wesleyan tradition of entire sanctification. In this article I hold up the theological doctrine of Union with God as the goal of the Christian life and review and contrast how Wesley and John of the Cross approached the issue. UThile these two spiritual masters outline differing views of the path to perfection in love, they both, nevertheless, continue to inspire and offer the light of Christ to Christians seeking full renewal in the Image of God, cleansing from sin, and filling with the pure love of God.